Prediction of treatment outcomes for personality disordered offenders. Issue 4 (4th November 2014) - Archibald, Sarah-Jane; Campbell, Colin; Ambrose, Derval
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Evidence has shown associations between personality disorder (PD) and poor treatment outcomes. The purpose of this paper is to: first, establish which risk assessment method (i.e. structured professional judgement or actuarial) is most reliable for predicting treatment outcomes for individuals with PD. Second, determine whether individuals identified as high risk are more likely to have poorer treatment outcomes. Third, determine if engagement in treatment helps to reduce risk assessment scores. Design/methodology/approach – In total, 50 patients were recruited from a medium secure forensic PD service. Their risk was assessed using one structured professional judgement instrument (the HCR-20) and one actuarial instrument (the RM2000). The study used a retrospective cohort design. Findings – Overall, the HCR-20 was a better predictor of treatment outcome than the RM2000. Personality-disordered offenders with high HCR-20 scores are at an increased risk of adverse treatment outcomes. Research limitations/implications – This investigation used a small, non-randomised sample of male patients with PD at one South East England medium secure unit. The data were over-represented by white British males. Future research should compare PD offenders with non-PD offenders to investigate what factors best predict poorer treatment outcomes. Originality/value – The findings indicate that structured professional judgement approaches are more effective predictors of risk than actuarial measures for assessing patients with PD. This study therefore adds value to forensic services and to the risk assessment debate.